Clinical-epidemiological characteristics associated with discharge outcomes and seasonality among surviving patients with Guillain-Barré syndrome in a national third-level hospital, Lima, Peru - Victor Velásquez-Rimachi; Angélica Verónica López-Saavedra; Ethel Rodriguez-López; Hillary Elguera-Huaman; Kelly Meza; Carlos Alva-Díaz; Kevin Pacheco-Barrios (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Guillain-Barré syndrome (GBS) is an autoimmune disease that affects the peripheral nervous system. Severe motor deficit (SMD), respiratory impairment, cranial nerve involvement and autonomic dysfunction are associated with a poor prognosis. Objective: To investigate the association between the clinical-epidemiological characteristics and the discharge results among Peruvian patients with GBS. Methods: We carried out a retrospective observational study on patients with GBS who survived until discharge. We used the Brighton Collaboration’s criteria and considered Hughes Severity Scale (HSS) scores greater than two to be SMD. We defined the discharge results as an improvement if the HSS score decreased by at least one point from admission to hospital discharge and defined hospital stay as prolonged if > 14 days. Results: We analyzed 92 patients, among whom 70.7% were male. Quadriparesis (81.1%) and hyporeflexia (86.8%) were the most characteristic manifestations. We observed that more than half of the cases were in summer and winter. Gastrointestinal infections were associated with a higher proportion of prolonged stays. The proportion of improvement was lower among patients who had an SMD at hospital admission. We confirmed these results through fitting in multivariate models. Conclusions: The prolonged stay was related to previous gastrointestinal infection, while a less improvement in SMD individuals at admission. Prospective multicenter surveillance systems are needed for monitoring GBS cases in low-income settings like Peru.